Kultuurkritiek en die Hervormde benadering tot teologiebeoefening: "n Gestaltegewing en uitdaging - Beukes, Johann (HTS teologiese studies, 2003)
A critique of culture and the Hervormde approach to doing theology: A description and challengeThis article investigates the relation between a critique of culture and the theological approach which is detectable in the theological labour of the Nederduitsch Hervormde Kerk. This theological approach is being described with reference to the three main intellectual traditions that maintain this approach in an equivocal fashion, namely the ethical, confessional and dialectical traditions. After summarising the most prominent characteristics and claims of these traditions, the author proceeds to bring this approach in relation to aspects of contemporary critique of culture.